Um modelo algébrico para a lógica modal KD - Feitosa, Hércules de Araujo; Soares, Marcelo Reicher; Lázaro, Cristiane Alexandra (Cognitio: Revista de Filosofia, 2022)
Deontic logic is a branch of symbolic logic interested in notions such as obligatory, permissible, optional, ought, and others similar. There are some equivalent ways to present the Standard Deontic Logic or KD. In this paper, we will mention some of them and highlight one that is of interest. With this presentation we can propose a simple algebraic model for the Standard Deontic Logic.